A Comprehensive Review on the Effects of Laser Photobiomodulation on Skeletal Muscle Fatigue in Spastic Patients - Sadi F. Stamborowski; Fernanda Púpio Silva Lima; Patrícia Sardinha Leonardo; Mário Oliveira Lima (International Journal of Photoenergy)
Peripheral muscle fatigue is a common experience in daily life. Every individual at some point in their life has realized the inability to maintain muscle contraction, a phenomenon known as fatigue. Interestingly, neurological patients with peripheral sequelae such as spastic muscle contraction are able to remain in a pattern of muscle contraction for prolonged periods. The effects of laser therapy are already recognized in muscle contraction to delay skeletal muscle fatigue, prolong physical activity, and reduce delayed onset muscle soreness. However, the effects of photobiomodulation on neurological patients with muscular spasticity are still not well established. The present literature review seeks to recognize articles about the application of laser irradiation, also known as photobiomodulation, to patients with muscle fatigue and/or spastic palsy. To perform a literature review, we used the systematic review methodology for the literature search. The following keywords were searched: (skeletal muscle fatigue) AND (spastic patients) AND (low-level laser therapy OR low intensity laser therapy OR low energy laser therapy OR LLLT OR LILT OR LELT OR infrared laser OR IR laser OR diode laser), and these were used for search on the following databases: PubMed, Embase, Web of Science, BIREME, Scopus, and SciELO. Besides that, a literature review concerning on muscle physiology, fatigue, and LLLT was made. No language filter was applied, and altogether, 689 papers were identified. A group of 3 physiotherapists and 01 pharmaceutical scientist performed the literature review, and every exclusion was confirmed by at least two reviewers. After inclusion and exclusion criteria, 128 studies were included in this review. Conclusion, the LLLT can contribute to the recovery of spastic patients and muscles in fatigue. However, the real effect of laser photobiomodulation on muscle spasticity remains to be established. Only a much reduced number of clinical trials have been performed with a small number of participants. There is a lack of clinical trials from different research groups that could help to understand and elucidate the effects of laser in prolonged muscle contraction in spastic palsy.